Computing the duration of regimes for autoclave steaming of frozen wooden prisms under variable operating conditions in veneer production. Issue 6 (2nd November 2022) - Deliiski, Nencho; Niemz, Peter; Vitchev, Pavlin; Angelski, Dimitar; Tumbarkova, Natalia
ABSTRACT: An approach for calculation of the duration of regimes for intensive autoclave steaming of frozen wooden prisms in cases of dispatching interferences into the operating temperatures has been suggested. The approach is based on the use of two coupled personal mathematical models: a 2D non-linear model of the unsteady distribution of the temperature in frozen and non-frozen prismatic wood materials subjected to steaming and a model of the non-stationary thermal balance of autoclaves for steaming wood materials. Using the suggested approach, calculation of the duration of regimes for defrosting and heating of beech prisms have been carried out. The variables were an initial wood temperature of −20°C, moisture content of 0.6 kg·kg −1, and cross-section dimensions of the prisms 0.4 × 0.4 m; steaming autoclave with a diameter of 2. 4 m, length of 9.0 m, and loading level of 50% for the cases of lowering by the dispatcher the maximum temperature of the basic steaming regime from 130°C to 120, 110, and 100°C in the 3rd, 7th, and 11th hour of these regimes. The approach can be applied for developing optimized energy-efficient regimes for autoclave steaming of frozen wood materials with desired duration set by the dispatcher.